Visualizing aviation impacts: Modeling current and future flight trajectories with publicly available flight data. (August 2018) - Li, Max Z.; Suh, Daniel Y.; Ryerson, Megan S.
Highlights: Airport expansion and airspace changes affect surrounding noise and emission levels. Technical aviation knowledge deters citizen involvement in airport planning process. Our method generates airspace visualizations with publicly available data. Resulting airspace maps are easy-to-understand and customizable. Abstract: As the demand for air travel continues to grow both nationally and internationally, airports seek airfield expansions and new infrastructure to accommodate new aircraft movements. However, airport expansion initiatives – runway extensions and/or new runway construction – directly impact terminal airspace operations. A change in flight paths near the airport affects the population living proximate to the airport, increasing noise levels and exposure to pollutants emitted by low-altitude departures and arrivals. While airspace procedures and their impacts are well-understood by aviation stakeholders, they are often convoluted and technical in nature. To this end, we propose a methodology to visualize terminal airspace trajectories leveraging publicly available data and commonly-used software. The trajectories are extracted via polynomial regression and hyperbolic tangent interpolation is applied to reflect accurate final approach maneuvers. Final visualizations are rendered in ArcGIS, a geographic information system used by many Metropolitan Planning Organizations. These trajectory visualization modules can also be combined with external models that provide noise contour projections and emission level estimations. We present a case study of Chicago O'Hare International Airport (ORD) due to the contentious O'Hare Modernization Program. The resultant interactive and dynamic three-dimensional trajectory airspace maps for ORD rendered via ArcGIS are easy to understand and customize, allowing MPOs to package them into downloadable online modules. MPOs armed with these modules will bridge the critical gap between the technical knowledge presented by authorities touting airport expansions and the residents who are impacted by the expansions.